Culturability and concentration of indoor and outdoor airborne fungi in six single-family homes - Lee, Taekhee (2006)
In this study, the culturability of indoor and outdoor airborne fungi was determined through long-term sampling (24-h) using a Button Personal Inhalable Aerosol Sampler. The air samples were collected during three seasons in six Cincinnati area homes that were free from moisture damage or visible mold. Cultivation and total microscopic enumeration methods were employed for the sample analysis. The geometric means of indoor and outdoor culturable fungal concentrations were 88 and 102 colony-forming units (CFU) m(-3), respectively, with a geometric mean of the I/O ratio equal to 0.66. Overall, 26 genera of culturable fungi were recovered from the indoor and outdoor samples. For total fungal spores, the indoor and outdoor geometric means were 211 and 605 spores m(-3), respectively, with a geometric mean of I/O ratio equal to 0.32. The identification revealed 37 fungal genera from indoor and outdoor samples based on the total spore analysis. Indoor and outdoor concentrations of culturable and total fungal spores showed significant correlations (r = 0.655, p<0.0001 and r = 0.633, p<0.0001, respectively). The indoor and outdoor median viabilities of fungi were 55% and 25%, respectively, which indicates that indoor environment provides more favorable survival conditions for the aerosolized fungi. Among the seasons, the highest indoor and outdoor culturability of fungi was observed in the fall. Cladosporium had a highest median value of culturability (38% and 33% for indoor and outdoor, respectively) followed by Aspergillus/Penicillium (9% and 2%) among predominant genera of fungi. Increased culturability of fungi inside the homes may have important implications because of the potential increase in the release of allergens from viable spores and pathogenicity of viable fungi on immunocompromised individuals.